(untitled) (Bangladesh Heart Journal, 2017)
Background: Electrocardiographic diagnosis of a posterior wall myocardial infarction is difficult to accomplish by the standard 12-lead ECG. Early detection of posterior wall involvement in an inferior myocardial infarction is of paramount importance for the therapeutic outcome. The aim of this study is to assess the role of ST segment elevation in posterior wall leads (V7, V8, V9) on the admission ECG of acute inferior myocardial infarction, for the diagnosis of posterior wall myocardial infarction and the identification of infarct related artery as well as in-hospital outcome following thrombolysis. Methods: A total of 90 patients with acute inferior MI were enrolled by purposive sampling. On the basis of ST segment elevation in posterior leads (V7,V8,V9), study subjects were categorized into two groups: 45 patients of acute inferior MI with ST segment elevation in posterior leads as group I and 45 patients of acute inferior MI without ST segment elevation in posterior leads as group II. Coronary angiography was done during index hospital admission. Interpretation of coronary angiogram was done by visual estimation by two cardiologists to assess the severity of coronary artery disease. Severity of coronary stenosis was graded according to the number of major epicardial vessel with significant stenosis by vessel score and Friesinger score. After CAG, patients were evaluated for in hospital adverse outcome like heart block, cardiogenic shock, arrhythmia, and death. Results: Patients of PMI and non PMI groups were similar in terms of age and sex. Smoking and dyslipidemia (p=0.05) were significantly higher in PMI group. Mean RBS and Troponin-I difference were significantly (p<0.05) higher in group I. Majority of patients had ejection fraction 45-55% in both groups. Patients in group I showed more normal LVEF, than group II, which was statistically significant. This study provided the evidence that the ST segment elevation in posterior leads associated with more left circumflex (LCX) and posterior left ventricular brass (PLVB) involvement. Majority of the patients had vessel score 2, Friesinger score 5-10 in group I and vessel score 1, Friesinger score 1-4 in group II. Conclusion: ST segment elevation in posterior chest leads (V7, V8, V9) were associated with more in-hospital adverse outcome than those who had inferior MI alone. This group of patients had more PLVB involvement. Recording of posterior precordial leads appear to be beneficial for risk stratification and to locate the site of lesion in patients admitted with acute inferior myocardial infarction. Since it is inexpensive method, it may be used in any hospital. Bangladesh Heart Journal 2016; 31(2) : 58-64